Mental health in rock climbing - Christian Mikutta; Eva Allenbach; Christian Imboden (Bern Open Publishing, 2024)
Introduction Rock climbing is an increasingly popular sport in the alpine region. It consists of different disciplines such as sport climbing, trad climbing or bouldering. Besides the professionally organized Olympic disciplines of indoor lead/speed climbing and bouldering, there is a large number of athletes who participate in advanced outdoor climbing without professional supervision. Due to this, rock climbing is associated with specific risks and heterogenous attitudes towards risk-taking and management of emotional reactions such as fear. Rock climbing also contains some risk factors for mental health problems, such as the importance of the athlete's weight and the possibility of traumatic situations. Methods We systematically reviewed the current literature using the keywords "rock climbing» and eating disorder, depression, drugs, anxiety disorder, psychosis, bipolar disorder, ADHD, personality traits, and psychology. Results From the initial findings, we included 29 papers in the review. Discussion We found that rock climbers are at increased risk for eating disorders. Furthermore, there was a surprisingly high number of athletes who practiced the sport while under the influence of drugs. Several models of risk-taking behavior and neurobiological stress reactions are discussed. Finally, rock climbers showed some risk of becoming addicted to the sport. Conclusion: There is a lack of evidence regarding the prevalence and risk factors of psychiatric diagnoses in rock climbers. Further research is needed to support these athletes.